Loss of Communication — Loss of Control. On the Issue of Economic and Political Results of 2023 - I. A. Maksimtsev; N. M. Mezhevich; A. D. Khlutkov (Управленческое консультирование)
The political and economic results of 2023 are a further increase in the uncertainty and multivariability of world development. At the same time, in 2023, the impossibility of returning to the “brave old world” became obvious. The obstacle to this was not Russia or China, but the entire objectively established set of international relations, including in the economic sphere. The authors deliberately do not touch upon the problems of SVO, as they proceed from the fact that this is not the reason, but the result of accumulated contradictions of a global scale.